PENGARUH LATIHAN PASSING TRIANGLE PASIF DAN AKTIF TERHADAP ACCURACY PASSING DALAM PERMAINAN FUTSAL ANAK SEKOLAH DASAR - Soemantri, Rizky; Sudrazat, Adang; Rukmana, Anin (Fakultas Ilmu Keolahragaan Unimed, 2024)
Futsal is a sport played by 2 teams of 5 people and is a popular sport. Basic futsal techniques include passing, control, dribbling, shooting and heading. The experimental method was used by the researcher in this study. The research design used quasi-experimental